Tissue surface adaptation and retention of digital obturator after one year of use - Khadija Mohamed Abd El Salam khalaf; Hoda Mohamed Amin Rashad; Tamer Mohamed Nasr Mostafa (BMC, 2024)
Abstract Background Effect of aging on tissue adaptability and retention of digital obturator is still under investigation. Methods A maxillary Armany (class I) epoxy reference model was scanned to fabricate digital obturator fabricated from milled Co-Cr framework and 3D printed bulb. A color map of the scanned reference and digital obturator was made using Geomagic software to evaluate the accuracy of fit before and after cyclic loading using ROBOTA chewing simulator at 37,500, 75,000 and 150,000 cycles to simulate clinically 3-, 6- and 12-months chewing condition. Insertion-removal condition simulating the placement and removal of the obturator was done using repeated 360, 720 and 1440 cycles and retention was evaluated before and after the repeated cycles. Data were collected, tabulated and statistically analyzed using Statistical Package for Social Sciences (IBM SPSS Statistics 26). Student t-test and multi variable ANOVA test were used to detect significance. P-value < 0.05 was considered significant difference. Results For retention test: There was a significant difference between baseline and 3, 6 and12 months. For the tissue surface adaptation test: There was significant difference at all measured areas (P-value < 0.05) before and after application of load. Conclusion digitally designed and fabricated obturator was highly retentive and has excellent tissue surface adaptation upon fabrication, After application of load; reduction of retention and lack of tissue adaptation were resulted. The clinical implication of this manuscript is that digital obturator can be used successfully with the shortcomings of loosening retention and adaptation afterwhile. So, clinical trials should investigate the clinical acceptance of these shortcomings.